A New Numerical Solution of Maxwell Fluid over a Shrinking Sheet in the Region of a Stagnation Point. (16th August 2012) - Motsa, S. S.; Khan, Y.; Shateyi, S.
Abstract : The mathematical model for the incompressible two-dimensional stagnation flow of a Maxwell fluid towards a shrinking sheet is proposed. The developed equations are used to discuss the problem of being two dimensional in the region of stagnation point over a shrinking sheet. The nonlinear partial differential equations are transformed to ordinary differential equations by first-taking boundary-layer approximations into account and then using the similarity transformations. The obtained equations are then solved by using a successive linearisation method. The influence of the pertinent fluid parameters on the velocity is discussed through the help of graphs.